The impact of the Health Silk Road on Global South countries: insights from Brazilian health agents - Santiago, Anabela Rodrigues; Rodrigues, Carlos (Frontiers in Political Science, 2023)
Introduction China is currently ranked second in the world economy, and its political role in the global order has increased in recent decades. As part of one of its modern and emblematic international projects, the Belt and Road Initiative (BRI) is the Health Silk Road, which can be considered a branch officially launched in 2017. Driven by some external factors, the most important of which is the COVID-19 pandemic, the Health Silk Road (HSR) and Chinese public health policies have gained accrued relevance, especially in countries of the Global South, which have been the main partners of Chinese cooperation initiatives, not only in health. Methods This study is an exploratory exercise that reflects the potential gains resulting from Chinese- Global South cooperation in the health sector by analyzing the perceptions of Brazilian health agents in a contemporary period starting from 2013 to 2023, which is the first 10 years since BRI implementation. We intend to answer the following questions: Does Brazil benefit from health partnerships with China, specifically under the Health Silk Road, despite not having formally joined the BRI? What are the privileged health areas of implementation, and what are the gains? These questions were answered through interviews with Brazilian researchers from public institutions to obtain their perspectives and insights regarding the practical aspects of partnerships. Results and discussion The current partnerships established are not directly linked to BRI initiatives. Brazilian health agents are generally unaware of the BRI contours and, consequently, HSR. The model of cooperation identified is based on the theoretical premise that each stakeholder contributes their best assets. New potential research topics were identified from this exploratory research to reflect on the impacts of HSR and Chinese Health Assistance in the Global South. We suggest in-depth research on the influence of the health sovereignty concept on the global health performance of countries from the Global South.